The PENGARUH INDUKSI STIMULASI OKSITOSIN TERHADAP KEBERHASILAN PERSALINAN PERVAGINAM PADA IBU HAMIL POSTTERM - Manullang, Ester; Sesilia, Maslina (Midwifery And Complementary Care, 2022)
Background: The Family Planning Program (KB) is carried out in order to regulate the amount of intravenous oxytocin, which is a continuation of the induction of foley catheters and misoprostol. The induction of oxytocin stimulation and foley catheter is to open or soften the cervix. While the purpose of giving oxytocin is augmentation/stimulation, namely to stimulate contraction. Oxytocin is administered by mixing 2.5-5 units of oxytocin in 500 ml of crystalloid solution. Intravenous oxytocin begins with 8 drops per minute and is added 4 drops every 30 minutes with a maximum dose of 20 drops per minute. Objective: To determine the effect of oxytocin stimulation induction on the success of vaginal delivery in post-term pregnant women at the Samuel Maternity Clinic in 2020. Method: This type of research is analytic observational, which is research that tries to explore how and why health phenomena occur, then analyzes the dynamics of the correlation between the phenomenon of risk factors (influence) and effect factors (effects), thus this research is limited to observing not doing any manipulation or intervention. Conclusion: From the research results, there was a significant relationship between the type of induction and the type of delivery (p-value 0.071). The type of induction had a 1.73 times greater chance of experiencing vaginal delivery (95% CI 0.95-3.14). The parity factor showed a significant relationship with the type of delivery (p-value 0.015). Parity 1 had a 2.10 times greater risk of experiencing a CS labor than parity> 1 (95% CI 1.16-3.80). The results of the multivariate analysis showed that the parity factor had a greater effect than the oxytocin stimulation induction factor on the success of vaginal delivery.